PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL THINK PAIR SHARE BERBANTUAN MEDIA COUPLE CARD - Soleha, Soleha; Habaridota, Maha Lastasa Buju Basafpipana; Fathurrosi, Fathurrosi (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2023)
The purpose of this study is to reveal: (1) To find out the learning outcomes of students before using the think pair share model assisted by the couple card media in thematic learning sub-theme I Cultural Diversity of my Nation Class IV MI Tarbiyatus Shibyan Sungai; (2) To find out the learning outcomes of students after using the think pair share model assisted by the couple card media in Thematic learning Sub-theme I Cultural Diversity of My Nation Class IV MI Tarbiyatus Shibyan; (3) To find out whether there is an influence on learning outcomes through the application of the think pair share model assisted by the couple card media on Thematic Learning Sub-theme I Cultural Diversity of My Nation Class IV MI Tarbiyatus Shibyan. This research includes Classroom Action Research (CAR) while the approach uses a quantitative approach. the researchers concluded that: 1)The learning outcomes of fourth grade students of MI Tarbiyatus Shibyan on thematic Sub-theme I Cultural Diversity of my Nation before using the Think Pair Share model assisted by Couple Card media have not reached the minimum completeness criteria (KKM) this can be seen from the learning outcomes of all students who did not reach the KKM with an average overall score of only 32,6%; 2) There is an increase in the learning outcomes of fourth grade students of MI Tarbiyatus Shibyan in thematic learning Sub-theme I Cultural Diversity of my Nation after using the Think Pair Share model with the help of Couple Card media, in the first cycle there were 23 students out of 31 students who had achieved KKM with an average overall score of 85,3%. In the second cycle there was an increase in the average score to 95,2% and all students reached the KKM score; 3) There is a significant effect of using the Think Pair Share model with the help of Couple Card media on the learning outcomes of fourth grade students of MI Tarbiyatus Shibyan in thematic learning of Sub-theme I Cultural Diversity of my Nation. This can be seen from the increase in the average value which was initially 32,6% to 85,3% and continued to increase to 95,2%.